Penatalaksanaan Okupasi Terapi DalamAktivitas Menggunakan Beha Dengan Konsep Bobath Pada Pasien Stroke Hemiparesis Sinistra Di Klinik Sasana Husada - E. R. N, Hidayati,; Pratiwi, Arum; Aliya, Rita (Jurnal Vokasi Indonesia, 2018)
Stroke is brain attack due to vascular injury that can damage the brain permanently because of neurologist disorder. The purpose of this intervention is to improve patient's ability to wear bras according to Occupation Therapy's view. The method that will be used to improve the patient ability who suffer from function disorder, movement, and control due to the lesion in the central nerve system is Bobath Concept. By giving eight times intervention, it can be seen that there is improvement postural control and less pain in the shoulder area when it moved. The result of this shows that there is no improvement yet in patient ability wearing bra because of fracture experienced by the patient.